Relationship between the level of asthma control, lung function and bronchodilator response in asthmatic children on inhaled corticosteroids - Javier Mallol; Viviana Aguirre-Camposano; Alejandro Gallardo; Pablo Córdova (Monaldi Archives for Chest Disease, 2025)
This study evaluated tools for assessing asthma control in 149 children on inhaled corticosteroids, focusing on the Asthma Control Test (ACT) and the Global Initiative for Asthma criteria (GINAc). It also explored the role of lung function (LF) tests, including spirometry and bronchodilator response (BDR), in identifying uncontrolled asthma. The GINAc identified 65.8% of children as having uncontrolled asthma, compared to 25.9% by the ACT (p<0.001). Spirometry and BDR results did not differ significantly between controlled and uncontrolled asthma groups. However, abnormal LF was more frequent in children with uncontrolled asthma identified by GINAc (18.4%) than in those controlled (5.9%; p = 0.038). In ACT-identified uncontrolled cases, 18.2% had abnormal LF compared to 12.4% with controlled asthma (p=0.360). Similarly, BDR appeared in 17.3% of uncontrolled cases by GINAc and 11.8% in controlled cases, with 25% of ACT-identified uncontrolled cases showing BDR vs. 11.4% in controlled (p=0.037). Findings suggest GINAc detects more cases of uncontrolled asthma than ACT and highlights the potential value of including spirometry and BDR to complement asthma control questionnaires, mainly aiding in identifying controlled asthma cases with underlying abnormal LF or BDR.